2018
DOI: 10.1111/bcp.13541
|View full text |Cite
|
Sign up to set email alerts
|

Acenocoumarol as an alternative anticoagulant in a patient with warfarin‐related nephropathy

Abstract: Further prospectively designed studies are needed to consider acenocoumarol as an alternative therapy in warfarin-related nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…From the past decades, vitamin K antagonists have been shown to have anticoagulant properties. The most important vitamin K antagonists that are currently in use are dicoumarol warfarin, phenprocoumon, acenocoumarol and rivaroxaban [ 239 242 ]. However, risk of a recurrent event among patients with venous thromboembolism has shown to be decreased with rivaroxaban at either a treatment dose (20 mg) or a prophylactic dose (10 mg) than with aspirin, without a significant increase in bleeding rates [ 243 ].…”
Section: Platelets Hyperactivity In T2dmmentioning
confidence: 99%
“…From the past decades, vitamin K antagonists have been shown to have anticoagulant properties. The most important vitamin K antagonists that are currently in use are dicoumarol warfarin, phenprocoumon, acenocoumarol and rivaroxaban [ 239 242 ]. However, risk of a recurrent event among patients with venous thromboembolism has shown to be decreased with rivaroxaban at either a treatment dose (20 mg) or a prophylactic dose (10 mg) than with aspirin, without a significant increase in bleeding rates [ 243 ].…”
Section: Platelets Hyperactivity In T2dmmentioning
confidence: 99%
“…Over previous decades, it has been demonstrated that vitamin K antagonists possess anticoagulant characteristics. Dicoumarol, warfarin, phenprocoumon, acenocoumarol, and rivaroxaban are among the most significant vitamin K antagonists presently employed ( 188 ). Compared to aspirin, rivaroxaban reduced the risk of recurrence in patients with venous thromboembolism without significantly increasing the risk of bleeding ( 189 ).…”
Section: Role Of Mets On Platelet Hyperactivitymentioning
confidence: 99%
“…Pathological states before the development of ecchymosis include disorders of coagulation pathways and platelets in addition to causing hematoma formation and disorders of dermal connective tissues. 1,2…”
Section: Anticoagulant-induced Ecchymosismentioning
confidence: 99%